Role of Micro-finance in rural housing in Bangladesh: a comparative study of the housing fund (Grihayan Tahbil) and Grameen housing loan - Begum, Monoara (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2006.